Patrón de distribución y listado de especies de las lombrices de tierra (Annelida, Oligochaeta) en Colombia - Feijoo M., Alexander; Quintero V., Heimar; Fragoso, Carlos; García Moreno, Ana (Instituto de Ecología, A.C., 2020)
The checklist of earthworm species of Colombia and the patterns of distribution are presented. Data was obtained from collections made from 1872 to 2002. The information come from sporadic taxonomic registers and from some systematic studies conducted in hydrographic basins and savanna regions; both highlight the high diversity of the Andes mountainous areas. Most collections (93.2%) were carried out in the Andean region. The Colombian Oligochaeta comprises 113 species placed in nine families, 30 genera and six subgenera, of which 90 are native and 23 exotic. Most of the species are endemic of the Glossoscolecidae family. Andiodrilus is represented by the greatest number of species (25), while Martiodrilus with 19 species shows the highest habitatdiversity, including forests, pastures and even the páramo. Only two species of this family were cosmopolitan (P. corethrurus and O. elegans) currently inhabiting anthropic environments. The species of the other families, excepting Tumak hamenni and Dichogaster medellina, were eurytopic